Schedulability Analysis for Real-Time Task Set on Resource with Performance Degradation and Dual-Level Periodic Rejuvenations - Hua, Xiayu; Guo, Chunhui; Wu, Hao; Lautner, Douglas; Ren, Shangping (IEEE Transactions on Computers, 2017)
Researches in real-time scheduling often assume that the performance of a computing resource does not change overtime. However, as system softwares and system architectures become increasingly complex, resource performance degradation over time becomes more evident. In this paper, we study the schedulability of a hard real-time task set on a resource which has performance degradation over time with a known pattern and use both cold and warm periodic rejuvenations as countermeasures. Such resource model is referred to as P2D-resource model for performance degradation and periodic rejuvenation with dual-levels. In this paper, we study (1) the formal specification of the P2D-resource model, (2) P2D-resource supply analysis, and (3) task set utilization bounds of a P2D-resource under Earliest Deadline First (EDF) and Rate Monotonic (RM) scheduling policies.
10 citations (Crossref) [2023-10-31]
Keywords: Aging; Analytical models; Computational modeling; Degradation; EDF; P2D-resource model; P2D-resource supply analysis; RM scheduling policies; Real-time system; Real-time systems; Software; System performance; dept.csc; dual-level periodic rejuvenations; earliest deadline first; formal specification; periodic resource; program diagnostics; rate monotonic scheduling policies; real-time scheduling; real-time systems; real-time task set; resource performance degradation; schedulability analysis; scheduling; software aging; software architecture; software maintenance; software performance evaluation; software rejuvenation; system architectures; system softwares; task set utilization bounds